LEVANTAMENTO DE MELHORES PRÁTICAS DE CONSTRUTORAS CEARENSES - Böes, Jeferson Spiering; Rocha, Paulo Henrique; Cândido, Luis Felipe; Barros Neto, José de Paula Barros Neto (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This paper aims to present a survey of best practices of construction companies from Fortaleza, Brazil. A multiple case study was carried out in 17 construction companies associated of INOVACON (Program of Innovation in Building Construction Industry). 16 best practices were selected and explored in depth. Those practices were grouped in three categories: (i) design; (ii) Production Planning and Control; (iii) logistic, systems technology and construction processes. The 16 best practices were summarily presented identifying its applications and benefits. As contribution, this paper offer a landscape of the level of practices of the industrial sector of construction at Ceará. Moreover, this picture provides opportunities from improvements and indicates the tendencies of investment to improve the sector. Its observed that the main investments are focused in improvements on-site execution though infuse technology, new materials and systems of construction.